Protein-lipid interactions at membrane surfaces: a deuterium and phosphorus nuclear magnetic resonance study of the interaction between bovine rhodopsin and the bilayer head groups of dimyristoylphosphatidylcholine. - Ryba, N; Dempsey, C; Watts, A (1986)
Rhodopsin, isolated from bovine retinal rod outer segment disk membranes, has been reconstituted into bilayers of 1,2-dimyristoyl-sn-glycero-3-phosphocholine which was deuterated in the terminal methyl groups of the choline polar head group. By use of a mixed detergent system of cholate and octyl glucoside to solubilize the phospholipid and rhodopsin, 15 membrane complexes of predetermined phospholipid to rhodopsin mole ratios of between 350:1 and 65:1 have been produced by exhaustive dialysis and studied by a variety of techniques. Electron micrographs of replicas from freeze-fractured membrane complexes showed that the majority of the lipid, for all rhodopsin:phospholipid ratios, was contained in large bilayer vesicles with diameters in excess of 400 nm. Complexes produced with rhodopsin from frozen retina produced an absorption maximum at 478 nm after photobleaching whereas rhodopsin from fresh retina could be bleached more completely to an absorption maximum at 380 nm. Deuterium nuclear magnetic resonance (NMR) spectra from the lipid head groups of bilayers above the gel to liquid-crystalline phase transition temperature were shown to be sensitive in a systematic way to the presence of rhodopsin which could be bleached to 380 nm. The measured quadrupole splittings, taken as the separation of the turning points of the recorded NMR spectra, decreased from a value of 1.28 kHz for protein-free bilayers to approximately 0.40 kHz for bilayers containing 65 molecules of phospholipid for each rhodopsin at 32 degrees C.(ABSTRACT TRUNCATED AT 250 WORDS)